UPAYA MENINGKATKAN PENDAPATAN MASYARAKAT MELALUI PELATIHAN MENJAHIT - Sania Yuninda; Dewi Safitri Elshap; Prita Kartika (IKIP Siliwangi, 2022)
The background of this research is limited employment opportunities and the decline in people’s income. Especially in the community in the village of Padalarang, West Bandung Regency. The purpose of this study was to find out about sewing skills training in increasing people’s income. The method used in this study is a qualitative method, with data collection techniques through observation, interview and documentation. The research subjects were one manager, one instructor and three training perticipans, the Mekarsari Padalarang Course and Training Institute (LKP). The results of this study indicate that sewing training is one way to develop community creativity in increasing income. The discussion explains how sewing training at the Mekarsari Training Course Institute (LKP) teaches good, neat sewing and creates competent graduates for sustainability in the world of work. In conclusion, it can be concluded that sewing training held by the Mekarsari Padalarang Course and Training Institute is very necessary to increase the economic income of the community, sewing training is one of the accesses that becomes an economic source to help meet daily needs.